2022
DOI: 10.3390/su14010535
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation among SMEs: Does Gender Matter?

Abstract: The COVID-19 pandemic has highlighted and exacerbated some of the challenges that small and medium enterprises (SMEs) face in times of crisis, disrupting their operations, weakening their financial positions, and exposing them to a wide range of financial risks. While previous studies have viewed digital transformation as a vital source of innovation and productivity growth for economic recovery in SMEs, there has been limited focus on digital transformation in the regional context, with very little attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 71 publications
1
15
0
2
Order By: Relevance
“…According to the conclusions of this study, Australia is well ahead of the rest of the world in terms of digital sales before and after COVID-19. This conclusion gives support to research that concludes that business owners adapt to emergency situations and adopt new business models in order to capitalize on marketing opportunities (Alam et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…According to the conclusions of this study, Australia is well ahead of the rest of the world in terms of digital sales before and after COVID-19. This conclusion gives support to research that concludes that business owners adapt to emergency situations and adopt new business models in order to capitalize on marketing opportunities (Alam et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…For instance, Orser and Riding (2018) established that gender influences IT adoption and that women are more likely to adopt IT than men. Similarly, Alam et al (2021) found a significant difference in how female-and male-led businesses perceived digital transformation. In addition, a significant percentage of the respondents have a high level of educational attainment.…”
Section: Respondents Of the Study -mentioning
confidence: 94%
“…Oleh sebab itu transformasi digital menjadi sebuah urgensi bagi para pelaku usaha mikro, kecil, dan menengah (UMKM) (Bai et al 2021). Bentuk transformasi digital yang dapat dilakukan oleh UMKM yaitu mengaplikasikan e-commerce (Alam et al 2022) yaitu melakukan proses bisnis dan pemasaran melalui media internet (Satar et al 2019). Aplikasi e-commerce pada UMKM memberikan manfaat diantaranya mengurangi biaya pemasaran dan iklan, memasuki pasar global, memberikan pelayanan yang lebih baik kepada konsumen (Sedighi dan Sirang, 2018), meningkatkan produktivitas dan efisiensi (Alzahrani, 2019).…”
Section: Pendahuluanunclassified